Parents’ Autistic Personality Traits and Sex-Biased Family Ratio Determine the Amount of Technical Toy Choice - Lange-Küttner, Chris; Korte, Messiah A.; Stamouli, Christina (Frontiers in Psychology, 2019)
We investigated the effect of parents’ AQ, their sex and the sex of their children on their toy preference. In a computerized forced-choice shopping task, adults selected from cuddly and social role-playing toys (social toys), academic, music and sports toys (educational toys) and construction sets as well as cars (technical toys). A sex-balanced high and low AQ sample of 160 adults, consisted of groups of parents of sons only, daughters only, sons and daughters, as well as of a group of adults without children (non-parents). The standard toy preference was social toys < educational toys < technical toys. Low AQ women were the only group to make a significantly higher amount of educational and a lower amount of technical toy choices. The mere presence of just sons increased technical toy choice in this experiment, while the mere presence of just daughters reduced technical toy choice both in men and high AQ individuals.